The Effect of Strategic Service Quality Management and Strategic Human Resources Planning & Budgeting on the Effectiveness of Organizational Performance Mediated by Work Climate at the Main Base of the Indonesian Navy III Jakarta - Hermanto Hermanto; Kusnadi Kusnadi; Eddy Panjaitan; Willy Arafah (Universitas Trisakti, 2021)
The purpose of this study was to analyze the direct effect of Strategic Service Quality Management on Good Work Climate; Strategic Human Resources Planning & Budgeting on Work Climate; Strategic Service Quality Management on Organizational Effectiveness Performance; Strategic Human Resources Planning & Budgeting on Organizational Performance Effectiveness; Work Climate on Organizational Performance; indirect influence of Strategic Service Quality Management on Organizational Performance Effectiveness mediated by Work Climate and Strategic Planning Human Resources & Budgeting on Organizational Performance Effectiveness mediated by Work Climate. The population in this study were employees of Lantamal III Jakarta with a population sample of 172 respondents. The findings of this study are that there is an influence of strategic service quality management and strategic planning of human resources & budgeting on the effectiveness of organizational performance mediated by the good work climate and the seven hypotheses proposed are all proven to be accepted. Good Work Climate plays a very important role as mediation in improving Strategic Service Quality Management and Strategic Human Resources Planning & Budgeting on Organizational Performance Effectiveness.